Both coinfections of Penicillium marneffei and Cryptococcus neoformans in AIDS patient: a report of rare case. (24th September 2017) - Li, Yu-Ye; Saeed, Ummair; Wei, Sha-Sha; Wang, Li; Kuang, Yi-Qun
Abstract : Supplemental Digital Content is available in the text